Sentiment Analysis and Word Cloud Insights of Freelance Illustrators in the Dynamics of the AI Art Era using Atlas-ti - Wily Mohammad; Hanif Saifurrahman; Riska Nabila; Besar Agung Martono (Tinta Emas Publisher, 2023)
This qualitative research aims to explore the dynamics of business competition in the modern era, specifically within the realm of freelance illustration, in response to the emergence of AI Art. The study delves into the sentiments, perceptions, and concerns of freelance illustrators regarding AI Art's impact on their profession and the broader creative landscape. Employing a mixed-methods approach, encompassing Sentiment Analysis and Word Cloud analysis utilizing Atlas-ti software, the research captures the multifaceted viewpoints of 25 freelance illustrators. The Sentiment Analysis discerns a complex tapestry of sentiments, with 46% of participants expressing positive sentiments and 54% expressing negative sentiments concerning AI Art. Positive sentiments underscore AI Art's potential to democratize art, broaden creative horizons, and enhance accessibility. Conversely, negative sentiments revolve around apprehensions of job displacement, ethical dilemmas, and the potential erosion of traditional artistic skills. The Word Cloud analysis further dissects the most prevalent terms associated with each sentiment, offering insights into the central themes and concerns. These findings highlight the intricate interplay of emotions within the freelance illustration community which has more negative sentiments.